DEEPhide: A Text Steganography Encoder and Decoder Tool using Deep Learning - Soo, Kai Zhao; AHMAD KHALID, SHAMSUL KAMAL (Applied Information Technology And Computer Science, 2025)
Text steganography is crucial in ensuring secure communication, but existing tools often lack efficiency in decoding concealed messages. This project introduces DEEPhide, a deep learning-based text steganography encoder and decoder developed using CNN and RNN. DEEPhide leverages neural networks to analyze patterns in encoded text to predict method used to improve decoding accuracy and speed. This helps to reduce time cost comparing to traditional methods and enhance text steganography, resulting in more robust and intelligent secure communication tools.